Peningkatan Membaca Pemahaman Menggunakan Model Kooperatif Tipe Cooperative Integrated Reading and Composition (CIRC) di Sekolah Dasar - oktafiyenti, dona; Taufik, Taufina; mayarnimar, mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is motivated by the low skill of students in reading comprehension in class VI Elementary.This research is a classroom action research (PTK) which uses qualitative and quantitative approach.This result of this study indicate an increase in : (a) cycle I the percentage of teacher activitties 68,75  (good), cycle II 93,75 (very good) and percentage of student activities cycle I 68,75 (good), cycle II 93,75 (very good). (b) average result in the pre-cycle stage of cycle I 55,76 (enough), cycle II 84,61 (very good). (c) average result at the reading stage I 62,56 (good), cycle II 93,58 (very good). (d) average result in the post-cycle stage I  58,46 (enough), cycle II 77,30 (good). Based on the results of this study can be concluded that by using the models Cooperative type Cooperative Intagrated Reading and Composition (CIRC) can improve the skills of reading comprehension of sixth grade students SDN 43 Sangkir Lubuk Basung Agam Regency. Keyword : Reading Comprehension, Cooperative models type CIRC